Differences in Ca 15-3 and Homocysteine Levels in Patients with Benign Tumor and Breast Cancer - Mathink Toonov ANUGERAWATI; Indranila Kustarini SAMSURIA; I Edward Kurnia Setiawan LIMIJADI; Dwi RETNONINGRUM; Banundari RACHMAWATI (Modern Medicine)
More than 25% of women have complaints related to breast lumps during their lifetime and approximately 12% have breast cancer. Cancer antigen 15-3 and homocysteine can be used as biomarkers in breast cancer. Breast cancer produces pro-inflammatory cytokines that can lead to increased CA 15-3 levels and serum homocysteine levels. Objective: To investigate the differences in CA 15-3 and homocysteine levels between patients with benign tumors and breast cancer. Methods: Observational analytic study with a cross-sectional approach in 30 benign breast tumor patients and 31 breast cancer patients. Measurement of CA 15-3 levels using enzyme linked immunofluorescent assay (ELFA) and homocysteine using competitive enzyme linked immunosorbant assay (ELISA). Comparative tests used independent T test and Mann-Whitney test. The study was conducted in 2023 at Kariadi Hospital Semarang and Ken Saras Hospital Ungaran. Results: CA 15-3 levels in the benign breast tumor group had a median of 11.74 (2.00-40.00) U/mL, while the breast cancer group was 18.66 (7.22-168.97) U/mL (p = 0.001). Homocysteine levels in benign breast tumors had a median of 3.05 (0.10-11.50) µmol/L and in the breast cancer group was 9.90 (3.70-17.20) µmol/L (p = 0.0001). Conclusion: CA 15-3 and homocysteine levels were lower in benign breast tumor patients compared with breast cancer patients.